Stabilization for a Periodic Predator-Prey System. (16th January 2008) - Aniţa, Sebastian; Tarniceriu, Carmen Oana
Abstract : ?A reaction-diffusion system modelling a predator-prey system in a periodic environment is considered. We are concerned in stabilization to zero of one of the components of the solution, via an internal control acting on a small subdomain, and in the preservation of the nonnegativity of both components.